ANALISIS POLA KONSUMSI MASYARAKAT KOTA MALANG PASCA KENAIKAN HARGA BAHAN MAKANAN - Susilowati, Dwi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
The intention of this research are 1) To know how pattern consume society of malang city after the increase of price foodstuff? 2) How pattern consume society of malang city after increase of price of food-stuff compared to previously? and 3) Whether difference of pattern consume society of malang city before and hereafter the increase of price food-stuff? From result of research indicate that there is no change meaning to consume rice and soy (tempe/tofu) before and also after existence of increase of price. This matter give indication that consumption of rice and soy(tempe/tofu) of society is not affected by change (increase of price) remember that rice and soy (tempe/tofu) represent fundamental requisites. As suggestion for the government is shall the stock of soy and rice have to be taken care of don't be scarce in marketing. Rare of soy and rice (tempe/tofu) is disaster for society. For the government is obliged to control price so that did not be heavy against for the society especially the impecunious society.